Overexpression of Plasmodium berghei ATG8 by Liver Forms Leads to Cumulative Defects in Organelle Dynamics and to Generation of Noninfectious Merozoites - Christiane Voss; Karen Ehrenman; Godfree Mlambo; Satish Mishra; Kota Arun Kumar; John B. Sacci; Photini Sinnis; Isabelle Coppens (mBio, 2016)
ABSTRACT Plasmodium parasites undergo continuous cellular renovation to adapt to various environments in the vertebrate host and insect vector. In hepatocytes, Plasmodium berghei discards unneeded organelles for replication, such as micronemes involved in invasion. Concomitantly, intrahepatic parasites expand organelles such as the apicoplast that produce essential metabolites. We previously showed that the ATG8 conjugation system is upregulated in P. berghei liver forms and that P. berghei ATG8 (PbATG8) localizes to the membranes of the apicoplast and cytoplasmic vesicles. Here, we focus on the contribution of PbATG8 to the organellar changes that occur in intrahepatic parasites. We illustrated that micronemes colocalize with PbATG8-containing structures before expulsion from the parasite. Interference with PbATG8 function by overexpression results in poor development into late liver stages and production of small merosomes that contain immature merozoites unable to initiate a blood infection. At the cellular level, PbATG8-overexpressing P. berghei exhibits a delay in microneme compartmentalization into PbATG8-containing autophagosomes and elimination compared to parasites from the parental strain. The apicoplast, identifiable by immunostaining of the acyl carrier protein (ACP), undergoes an abnormally fast proliferation in mutant parasites. Over time, the ACP staining becomes diffuse in merosomes, indicating a collapse of the apicoplast. PbATG8 is not incorporated into the progeny of mutant parasites, in contrast to parental merozoites in which PbATG8 and ACP localize to the apicoplast. These observations reveal that Plasmodium ATG8 is a key effector in the development of merozoites by controlling microneme clearance and apicoplast proliferation and that dysregulation in ATG8 levels is detrimental for malaria infectivity. IMPORTANCE Malaria is responsible for more mortality than any other parasitic disease. Resistance to antimalarial medicines is a recurring problem; new drugs are urgently needed. A key to the parasite’s successful intracellular development in the liver is the metabolic changes necessary to convert the parasite from a sporozoite to a replication-competent, metabolically active trophozoite form. Our study reinforces the burgeoning concept that organellar changes during parasite differentiation are mediated by an autophagy-like process. We have identified ATG8 in Plasmodium liver forms as an important effector that controls the development and fate of organelles, e.g., the clearance of micronemes that are required for hepatocyte invasion and the expansion of the apicoplast that produces many metabolites indispensable for parasite replication. Given the unconventional properties and the importance of ATG8 for parasite development in hepatocytes, targeting the parasite’s autophagic pathway may represent a novel approach to control malarial infections.